A study on the success factors of women in construction industry in Kota Bharu, Kelantan - Noor Amalina, Abdull Manaf (2016)
The construction industry is one of the industries listed as a major contributor to the economic development of the country. The importance of the construction industry can be seen clearly through the involvement of industry and construction in various diverse fields to make Malaysia a developed nation. If viewed from then until now, the involvement of men in this industry has never diminished even more people interested in entering this field. But, there are also women show their excellence in the industry when given a chance to involved to be more competitive and to fight for women's empowerment and to be more active and productive in the construction industry in the country. The women nowadays are large groups that contribute to the national economy. Therefore, this research aimed to study the success factors of women in the construction industry and identify the challenges faced by women in construction industry. Using the Statistical Package for the Social Science (SPSS), the data set was analyzed to get the result and finding. Result shows that, many factor that contribute them to achieve goals and performance in the organization such as, reward, work environment and so on. Also the challenges that need to faced in this industry.